Shallot engaruh Ukuran Umbi Benih Yang Dibelah Vertikal dan Frekuensi Atonik Terhadap Pertumbuhan Dan Hasil Bawang Merah (Allium cepa L.) - Raharjo, Krisantus Tri Pambudi; Lelang, Maria Afnita (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
ABSTRACT The research aimed to determine the effect of vertically split of the shallot bulbs size and atonic frequency on shallot growth and yield was carried out on field at the Faculty of Agriculture, Science and Health, University of Timor, using a two-factor Completely Randomized Design (CRD). The first factor is the size of the bulbs, i.e., small size (D1), medium size (D2), and large size (D3). The second factor is the frequency of Atonic PGR (plant growth regulator) application (1.5 mL/L water), i.e.; 1 (F1), 2 (F2), and 3 (F3) times. The results of the research showed that even though there was no interaction between treatments, the use of medium sized of shallot bulbs with the frequency of Atonic PGR application 2 times was optimal to increase maximum growth and yield, including: number of leaves, leaf area, fresh weight of the plant, fresh weight of the waste, and dry weight of the waste, and dry weight of the bulbs (41.20 g). The interaction resulted in the fresh weight of the plant (59.49 g) and the fresh weight of the bulb (48.90 g) higher than other treatment. Keywords: